Heart–brain team approach of acute myocardial infarction complicating acute stroke: Evidencing the knowledge gap - Li, Na; Tian, Xin; Guo, Yongzheng (Brain-X, 2023)
[...]cardiovascular and bleeding outcomes in this study were subjected to be affected by variable guidelines for coronary revascularization and antithrombotic and lipid-lowering therapies from 2007 to 2020. [...]the effect of conventional therapy was absent for comparison with the heart–brain team approach in the present study. [...]the paper by Suzuki et al. provided evidence of an important knowledge gap, where additional research is eagerly needed to help clinicians make personalized treatment decisions for treatment with the heart–brain team approach in patients with AMI-CAS.